EXAMINING JOB DEMANDS, ENGAGEMENT, AND JOB SATISFACTION AMONG HOSPITAL STAFF - Ummu Kalsum; Salwah Suardi; Indriani Mentaruk; Andi Nurul Azizah (Smart Education, 2026)
Abstract: Quality healthcare can only be achieved through highly motivated and professionally competent workers. Hospitals are dynamic work environments, where healthcare workers face long hours, heavy workloads, and high pressure that can affect their engagement and job satisfaction. This study aims to analyze the effect of job demands (JD) on work engagement (WE) and its impact on job satisfaction (JS) among healthcare workers at Haji Hospital in Makassar, South Sulawesi Province. This study uses a quantitative approach with a cross-sectional design. A total of 244 respondents were selected using random quota sampling. The data were analyzed using Path Analysis with SPSS AMOS 26 software. The results showed that job demand had a significant effect on work engagement (p=0.028) and job satisfaction (p=0.027). However, there was no indirect effect of job demand on job satisfaction through work engagement (p=0.114). These findings indicate that increasing work engagement and job satisfaction among hospital staff is more effective through the direct influence of job demands. Employees tend to be more engaged and satisfied when faced with high job demands. Keywords: Job demand; Work engagement; Job satisfaction; Health services; Hospitals Abstrak: Pelayanan kesehatan yang berkualitas hanya dapat dicapai melalui keberadaan tenaga kerja yang memiliki motivasi tinggi dan kompetensi profesional. Rumah sakit merupakan lingkungan kerja yang dinamis, di mana tenaga kesehatan menghadapi jam kerja panjang, beban kerja berat, dan tekanan tinggi yang dapat memengaruhi keterlibatan serta kepuasan kerja. Penelitian ini bertujuan menganalisis pengaruh tuntutan pekerjaan (Job Demand/JD) terhadap keterlibatan kerja (Work Engagement/WE) dan dampaknya terhadap kepuasan kerja (Job Satisfaction/JS) pada tenaga kesehatan di RSUD Haji Provinsi Sulawesi Selatan. Penelitian ini menggunakan pendekatan kuantitatif dengan desain cross-sectional. Sebanyak 244 responden dipilih melalui metode random quota sampling. Data dianalisis menggunakan Path Analysis dengan perangkat lunak SPSS AMOS 26. Hasil penelitian menunjukkan bahwa job demand berpengaruh signifikan terhadap work engagement (p=0,028) dan kepuasan kerja (p=0,027). Namun, tidak terdapat pengaruh tidak langsung antara job demand terhadap kepuasan kerja melalui work engagement (p=0,114). Temuan ini menunjukkan bahwa peningkatan work engagement dan kepuasan kerja staf Rumah sakit lebih efektif melalui pengaruh langsung dari job demand. Pegawai cenderung lebih terlibat dan puas ketika menghadapi job demand yang tinggi. Kata kunci: Tuntutan Pekerjaan; Keterlibatan Kerja; Kepuasan Kerja; Tenaga Kesehatan; Rumah Sakit